Enhancing the practice of immigrant child welfare social workers in the United States. (March 2019) - Lin, Ching-Hsuan; Wiley, Angela R
Responding to the needs of growing immigrant populations, many US social service sectors have recruited bilingual and bicultural practitioners, including immigrants. However, little is known about the immigrant social workers. This article explores the practice context of immigrant child welfare social workers in the United States. First, acculturation theory is applied to frame the experiences of US immigrants. Second, we explore professional development of practitioners working with immigrant families. Third, we discuss the intersectionality connecting immigration and social work professionalization. We conclude that the immigration and acculturation experiences of immigrant social workers are unique strengths for working with immigrant populations.